The influence of Attitude and Perceived Behavior Control on purchase intention at Sambal Bakar (restaurant) - Muhammad Faiz Zidan; Ahmad Nuh; Huslan Husada (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
This study aims to examine the influence of attitude, trust, subjective norms, personal innovativeness, and perceived behavior control on purchase intention at Sambal Bakar, a restaurant. The study will employ the Theory of Planned Behavior (TPB) to understand the relationships between these variables and their impact on customers' intentions to purchase food from the restaurant. The research will be conducted on a sample of customers who have previously visited Sambal Bakar, and data will be collected using a self-administered questionnaire. The findings of this study will provide valuable insights into the factors that influence purchase intention at Sambal Bakar and help restaurant managers develop strategies to improve customer satisfaction and loyalty.